2017
DOI: 10.14202/vetworld.2017.1367-1377
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and immunological changes in transition dairy cows: A review

Abstract: Smooth transition from pregnancy to lactation is important for high productive and reproductive performance during later postpartum period in dairy animals. On the other hand, the poor transition often leads to huge economic loss to dairy farmers due to compromised production and reproduction. Therefore, understanding the causes and consequence of metabolic changes during the transition period is very important for postpartum health management. In this review, metabolic changes with reference to negative energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 59 publications
4
125
0
7
Order By: Relevance
“…Dairy cows are characterized by endocrine and metabolic changes to meet out the milk production during lactation (Goff & Horst, ). Thus, the incidence of metabolic disorders, mammary gland infections and reproductive disorders (such as dystocia, retained placenta, cystic ovarian disease, and uterine infections) are frequent in high‐producing herds (Wankhade et al, ). However, in mouse, the supplementation of 100 ng/ml of AMH into IVM medium together with FSH and epidermal growth factor (EGF) improves oocyte competence (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dairy cows are characterized by endocrine and metabolic changes to meet out the milk production during lactation (Goff & Horst, ). Thus, the incidence of metabolic disorders, mammary gland infections and reproductive disorders (such as dystocia, retained placenta, cystic ovarian disease, and uterine infections) are frequent in high‐producing herds (Wankhade et al, ). However, in mouse, the supplementation of 100 ng/ml of AMH into IVM medium together with FSH and epidermal growth factor (EGF) improves oocyte competence (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Schuberth, 2 and Ch. Kühn 6,11 diseases also show metabolic disorders (Raboisson et al, 2014;Vercouteren et al, 2015;Mostert et al, 2018), and several authors have demonstrated the connection between the capacity of immunological defense strategies and metabolic regulatory mechanisms (Overton and Waldron, 2004;Roche et al, 2017;Wankhade et al, 2017). In the future, it will be important to reconcile economic efficiency and ethical requirements by breeding cows that are high-yielding as well as healthy and long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…However, the feed intake of heifers and dry cows usually declines in the late dry period relative to their energy requirements (Grummer, 1995;Huzzey et al, 2007), triggering the beginning of the NEB (Butler, 2003). The decrease in prepartum DMI can be attributed to digestive, hormonal, physiological and immunological factors related to this period, and to the rapid growth of the foetus, which takes up the abdominal space, thereby decreasing the rumen volume (Jouany, 2006;Wankhade et al, 2017). Everitt (1964) reported that the foetus of a ruminant is more vulnerable than that of many other species to maternal undernutrition stresses, which impede normal foetal growth.…”
Section: Energy Sources During the Dry Periodmentioning
confidence: 99%
“…When dairy cows experience a NEB, their immune system is likely to be compromised (Mallard et al, 1998;Wankhade et al, 2017). The level of impairment and the degree of reclamation of postpartum immune competence are influenced strongly by the extent and duration of the NEB around calving (Pyörälä, 2008;Wathes et al, 2009), making cows in a severe NEB more vulnerable to infections caused by pathogenic organisms (Goff, 2006;Wathes, 2012).…”
Section: Negative Energy Balance and Postpartum-related Disorders In mentioning
confidence: 99%
See 1 more Smart Citation